A digitally enhanced ripple emulated residual current mode dynamic on time controlled buck converter with fast transient response - Sivakumar Kumaraguruparan; Konguvel Elango (Results in Engineering, 2025)
This paper proposes a digitally enhanced ripple-emulated residual current controlled buck converter. Current mode control (CMC) offers advantages in buck converters compared to voltage mode control. However, analog steady-state current control suffers from steady-state errors, frequency variation, and poor output voltage regulation. To overcome these limitations, digital control provides improved precision but introduces stability issues due to inherent delays. To address this, a residual current control scheme with an enhanced ripple emulator is introduced. The residual current mode combined with a dynamic on-time (DOT) strategy enhances stability and enables fast transient response with reduced settling time. The enhanced ripple emulator further reduces steady-state error and improves the control response. A comprehensive mathematical model is developed, and the performance and stability of the system are evaluated using MATLAB Simulink. Experimental results show that the proposed converter achieves a minimum recovery time of 0.65 μs and a voltage overshoot of 38 mV for a load transition from 0.1 A to 1 A at a switching frequency of 500 kHz. For the reverse step from 1 A to 0.01 A, the converter exhibits an undershoot of 36 mV and a recovery time of 0.5 μs. Moreover, the approach significantly reduces operating frequency variation to 0.8%, demonstrating enhanced robustness compared to conventional techniques.